Intergenerational Occupational Mobility in Rural Economy : Evidence from Nepal and Vietnam - Emran, M. Shahe (2012)
This paper presents evidence on intergenerational occupational mobility from agriculture to the nonfarm sector using survey data from Nepal and Vietnam. In the absence of credible instruments, the degree of selection on observables is used as a guide to the degree of selection on unobservables, a la Altonji et al. (2005) to address the unobserved genetic correlations. The results show that intergenerational occupational mobility is lower among women in both countries, and is lower in Nepal compared with Vietnam. In the case of Nepal, strong evidence favors a causal role played by the mother's nonfarm participation in the daughter's occupation choice, possibly because of cultural inheritance in a traditional society.